PASTORAL COUNSELING TO PARENTS WITH CHILDREN IN PROMISCUITY - Tri Prapto Suwito; Yonas PAP (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2022)
Parents have full responsibility for their children, but the circumstances of the times are always changing influenced by technological advances and all its effects, so that children can be out of control because parents are busy, circumstances can vary, maybe rich parents with good business for finance, but attention to children lags behind, this can make children seek attention elsewhere, or look for people who can love themselves. Likewise, from parents with a mediocre economy or even less, the situation can have a similar effect, although it is possible that from the two economic conditions there are many who are harmonious and successful. The release of parental control can make children plunge into promiscuity, the purpose of this study is to provide understanding to parents who have experienced various things about children who hang out freely.